Pentingnya Penanaman Karakter Pada Peserta Didik Dalam Dunia Pendidikan Di Era Globalisasi - Madyan Madyan; Pirwanto Pirwanto; Habib Baihaki; Suparno Suparno; Dwi Kartika Sari; Wasnadi Wasnadi (STEKOM PRESS, 2024)
Character cultivation is a form of human activity in which there are actions that educate and are intended for the next generation. The aim of character education is to continuously improve the individual's self and train their abilities in order to lead a better life. Character education helps improve students' academic achievement. Some children cannot form a strong character for themselves elsewhere. Can form individuals who value and respect other people and can live in a pluralistic society. At this time, the very high flow of globalization often has negative impacts. Many students today are experiencing a moral crisis which results in negative behavior in society. For example, violence, relationships and manners. The role of parents, teachers and the community is very much needed in this case to guide and monitor the flow of globalization so that students can make the best use of this era of globalization.